Band-pass Filter with Harmonics Suppression Capability - Izni Husna Idris; Mohamad Rijal Hamid; Kamilia Kamardin; Mohamad Kamal A. Rahim; Farid Zubir; Huda A. Majid (Institute of Advanced Engineering and Science, 2018)
This paper presents a Band-pass Filter (BPF) with a very wide suppressions band. The filter design is based on a modified U-shaped slot. Two pair of U-shaped slots is used to ensure that the filter can suppress the unwanted frequencies up to 4th harmonics. In order to achieve sharp skirt, two transmission zeroes are created near the passband area. Additional transmission zeroes are introduced to deepen the stopband area. Therefore, the passband range starts from 1.3 to 3.3 GHz and the stopband range from 3.3 GHz up to 9 GHz are achieved. The filter performances are verified through simulated and measured results.